Presence at any Distance: Updating the Virtual in Times of Emergency Teaching Practices - Dias, Vanina (2023)
This article reports a research developed with higher education professors during the period of the Covid-19 pandemic, questioning how these professors made the transition from face-to-face classes to remote classes. The concepts of presence (or social presence) developed by Biocca (1997) and virtuality developed by Deleuze and Guattari (1995) as well as Levy (2003) were taken as guides. The testimonies were collected through an online form, sent by Google Forms, in May 2020. 57 teachers responded to the form. Based on the content analysis proposed by Bardin (2011), the following categories were chosen: the human interfaces present in the mediation process; artificial interfaces as a support to the learning process. In the light of these categories, it was noticed that 30% of the content of the testimonies given by the teachers concerns the use of artificial interfaces and 70% are related to human interfaces. And yet, whether it is remote, distance or online education, despite teachers and students being physically in other spaces, the use of virtual technologies significantly increases the power of contact and communication. In this sense, technology becomes a powerful way that can lead to learning.   Keywords: Emergency remote teaching. Virtuality. Presence.